International study on energy end-use data among industrial SMEs (small and medium-sized enterprises) and energy end-use efficiency improvement opportunities - Thollander, Patrik; Paramonova, Svetlana; Cornelis, Erwin; Kimura, Osama; Trianni, Andrea; Karlsson, Magnus; Cagno, Enrico; Morales, Inés; Jiménez Navarro, Juan Pablo (Elsevier, 2015)
The industrial sector is important to study in terms of improved energy efficiency, being one of the major energy-using sectors and responsible for a major share of CO2 emissions. The energy end-use (EEU) in the industrial sector is complex in general as processes are intertwined and interrelated. Moreover, bottom-up data of EEU on an aggregated level is scarce. Data for total energy supply like electricity, oil, coal, and natural gas exists but bottom-up data of what processes these energy carriers are used in, and moreover, where the major potential for implementation of energy efficiency measures (EEMs) exists, is less prevalent. This holds in particular for industrial small and medium-sized enterprises (SMEs). This makes policy formulation and design for industry a great challenge. Knowledge on where and how energy is used, as well as where opportunities for improvement exist, may provide good support for developing the most effective policies. Therefore, the aim of this study has been to present and compare available bottom-up energy data for industrial SMEs in four countries, namely Belgium, Italy, Japan and Sweden. Results show that the existence and quality of bottom-up EEU data differs largely between the countries and the development of a general taxonomy of structuring EEU data as well as EEMs is needed. Without the development of such a general taxonomy, the deployment level of EEMs and carbon dioxide emission reductions is unlikely to ever reach its full potential as knowledge is missing on how large the potential is, in which processes the major potential is found, how far industry has reached in terms of deployment levels, and in which areas future energy policies are needed. In conclusion, this paper of EEU and EEM in industrial SMEs addresses the high importance of future research in creating a harmonized data categorization, as this will greatly support the transition towards sustainable industrial energy systems.
Keywords: Energía - Conservación; SME; Industry; Energy efficiency; Energy audit